Promoting Caries-Free Program by having Regular 6-Month Dental Check-up in Ketabang Area, Surabaya - Sosiawan, Agung; Adla, Karina Awanis; Zuhdi, Nadya Adina; Karimah, Zalfa; Maharani, Gita Alethea Kristi; Krissanti, Theresa Dian; Sembadani, Yuliana Merlindika; Pratama, Innocencio Kresna; Rachmawati, Almira; Nurrezeki, Andi Adani; Detalicia, Callista Gladys Fionna; Syahdryani, Zhafira Putri (Faculty of Dental Medicine Universitas Airlangga, 2020)
Background: An epidemiological study conducted in two kindergartens located in Ketabang and Embong Kaliasin reported that 63% of kindergarteners were affected by dental caries. The study also found that only 8% of them received dental treatment. The remaining 92% of kindergarteners never had dental treatment due to uncovered health insurance, unavailability of parents during working days and hours, mother's education level, mother's medical history, paternal support in dental and oral health care. Promotive, preventive, and referral efforts for dental and oral health can be done by empowering UKGS teachers in the kindergarten concerned and in collaboration with local public health center routine 6-month dental check-up. Purpose: To promote dental health education for children and forming the habit of visiting dentist for dental check-up. Methods: This program was intended to support UKGS teachers' roles and encourage the mother to admit their children for a dental check-up. The dental check-up results of Dharma Putra kindergarteners were then recorded to the report. The report consisted of the prioritized tooth to treat, treated tooth, and treatment fee. Results: The dentists have recorded the examination results on the report sheet and informed the parents about their children's dental and oral health status. The UKGS teacher then scheduled follow-up appointment per group per week for dental treatment. 3 out of 3 kindergarteners attended the follow-up appointment. Conclusion: This program is effective to promote children to come to dentist.